Advance directives in the emergency department. Issue 3 (7th April 2020) - Baker, Eileen F.; Marco, Catherine A.
Abstract: Advance directives are documents to convey patients' preferences in the event they are unable to communicate them. Patients commonly present to the emergency department near the end of life. Advance directives are an important component of patient‐centered care and allow the health care team to treat patients in accordance with their wishes. Common types of advance directives include living wills, health care power of attorney, Do Not Resuscitate orders, and Physician (or Medical) Orders for Life‐Sustaining Treatment (POLST or MOLST). Pitfalls to use of advance directives include confusion regarding the documents themselves, their availability, their accuracy, and agreement between documentation and stated bedside wishes on the part of the patient and family members. Limitations of the documents, as well as approaches to addressing discrepant goals of care, are discussed.